Intra-Abdominal Pressure Correlates with Extracellular Water Content - Dąbrowski, Wojciech (PLoS One, 2015)
BACKGROUND: Secondary increase in intra-abdominal pressure (IAP) may result from extra-abdominal pathology, such as massive fluid resuscitation, capillary leak or sepsis. All these conditions increase the extravascular water content. The aim of this study was to analyze the relationship between IAP and body water volume. MATERIAL AND METHODS: Adult patients treated for sepsis or septic shock with acute kidney injury (AKI) and patients undergoing elective pharyngolaryngeal or orthopedic surgery were enrolled. IAP was measured in the urinary bladder. Total body water (TBW), extracellular water content (ECW) and volume excess (VE) were measured by whole body bioimpedance. Among critically ill patients, all parameters were analyzed over three consecutive days, and parameters were evaluated perioperatively in surgical patients. RESULTS: One hundred twenty patients were studied. Taken together, the correlations between IAP and VE, TBW, and ECW were measured at 408 time points. In all participants, IAP strongly correlated with ECW and VE. In critically ill patients, IAP correlated with ECW and VE. In surgical patients, IAP correlated with ECW and TBW. IAP strongly correlated with ECW and VE in the mixed population. IAP also correlated with VE in critically ill patients. ROC curve analysis showed that ECW and VE might be discriminative parameters of risk for increased IAP. CONCLUSION: IAP strongly correlates with ECW.